Faktor Risiko Neuropati Diabetik pada Penderita Diabetes Melitus Tipe 2 - Faiqotunnuriyah Faiqotunnuriyah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Diabetic neuropathy is a serious complication in diabetes mellitus sufferers which is caused by nerve damage, especially in the legs due to excessive blood sugar levels. The purpose of this study was to determine what factors are associated with the incidence of diabetic neuropathy in type 2 diabetes mellitus sufferers at Ungaran Hospital. This type of research is analytic observational using a case control study design. The samples were 25 cases and 25 controls who were selected using purposive sampling technique. The instrument used was a structured questionnaire. Data were analyzed using the chi square test and logistic regression with SPSS 16. The results showed that there was a relationship between hereditary history (OR = 3.78; 95% CI = 1.17-12.19), long suffering from diabetes (OR = 7.87; 95% CI = 2.07-29.94), history of dyslipidemia (OR = 3.18; 95% CI = 1.00-10.17), hypertension status (OR = 3.18; 95% CI = 1, 00-10.17), dietary adherence to DM (OR = 3.18; 95% CI = 1.00-10.17) and history of DM treatment (OR = 0.24; 95% CI = 0.06-0, 92) on the incidence of diabetic neuropathy in type 2 diabetes mellitus sufferers at Ungaran Hospital. Keywords: Diabetic Neuropathy, Risk Factors, DM Type 2